Quality of life of caregivers of octogenarians: a study using the WHOQOL-BREF - Silva Coura, Alexsandro; Alves Nogueira, Camila; Paulino Alves, Fabiana; da Silva Aragão, Jamilly; de França, Inacia Sátiro Xavier; Aires Silva Medeiros, Kaio Keomma (Investigación y Educación en Enfermería, 2015)
Objective. To evaluate the quality of life of octogenarians and to identify the domains related to quality of life and health. Methodology. A cross-sectional, quantitative study conducted in 2010 in the Family Health Units of Campina Grande/PB, Brazil. The study sample consisted of 52 subjects that met the eligibility criteria of: 18 years or older, being a lay caregiver of octogenarians, and having no apparent cognitive problem. A questionnaire containing a sociodemographic section and the WHOQOL-BREF that is composed of two questions about the perceptions of quality of life and health, and 24 on the physical, psychological, social relationships and environmental domains. The Cronbach’s-alpha test and the logical regression analysis of the data were conducted using SPSS. The project was approved by the Research Committee of the Center for Development and Higher Education (CAAE no0490.0.133.000-08). Results. The Cronbach’s alpha was 0.72, attesting to the reliability of the instrument used. The domain scores were: environmental (59.43), psychological (59.01), social relationships (46.77) and physical (43.86), whose values indicate dissatisfaction of subjects with regard to aspects related to quality of life. The environmental domain was correlated with quality of life (p=0.014) and the physical domain with perceptions of health (p=0.019); the daily safety and pain aspects had the highest correlations with quality of life (p=0.001). Conclusion. The perception of the caregivers regarding quality of life was not good. The environmental and physical domains had the highest correlations with quality of life and health. How to cite this article: Coura AS, Nogueira CA, Alves FP, Aragão JS, França ISX, Medeiros KKAS. Quality of life of caregivers of octogenarians: a study using the WHOQOL-BREF. Invest Educ Enferm. 2015; 33(3):